(untitled) (Ustozlar uchun, 2026)
This article analyzes the conflict between romantic love and social status in Jane Austen’s novels. It explores how personal desires clash with Regency-era social expectations regarding wealth, lineage, and class preservation. Through characters like Elizabeth Bennet and Anne Elliot, the study highlights women’s economic vulnerability and the psychological toll of social pressure, demonstrating that Austen championed emotional compatibility as essential for true marital stability.